2019
DOI: 10.1111/jan.14190
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of adherence to diabetes self‐care behaviours: Evidence from low‐ and middle‐income countries

Abstract: Aims To determine diabetes patient's adherence to five self‐care behaviours (diet, exercise; medication, self‐monitoring of blood glucose [SMBG] and foot care) in low‐ and middle‐income countries. Design Systematic review. Data sources We searched MEDLINE, CINAHL, PUBMED, SCOPUS, PsycINFO, EMBASE, Cochrane library and EMCARE for the period January 1990 – June 2017. Review Methods Title, abstract and full text screening were done according to eligibility criteria. A narrative synthesis of the literature was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 89 publications
4
71
2
3
Order By: Relevance
“…This variation probably related to improved public awareness toward the benefit of physical activity to control chronic diseases including diabetes through weight reduction. 6,32,33 The overall prevalence of good adherence to self-care behaviors in this study was 42.7%. This finding was higher than the finding of a study conducted by Ayele; et al found 39.0% of diabetes patients adhered to recommended self-care practices.…”
Section: Discussionmentioning
confidence: 63%
“…This variation probably related to improved public awareness toward the benefit of physical activity to control chronic diseases including diabetes through weight reduction. 6,32,33 The overall prevalence of good adherence to self-care behaviors in this study was 42.7%. This finding was higher than the finding of a study conducted by Ayele; et al found 39.0% of diabetes patients adhered to recommended self-care practices.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, the losses relating to achieving glycemic control are less explained by inadequacy of health systems' resources and mostly linked to barriers to patients' adherence. There are several factors that may affect the level of adherence Apart from the limited access to support services, which has been reported as a leading health system's barrier to adherence and lack of health insurance, medicines, and affordability of dietary recommendations ( 60 ), there are difficulties of changing long-term behaviors or changing food choices and eating habits based on cultural meaning of food, social pressure, and so on ( 61 , 62 ). This finding underlines the need for understanding the barriers and facilitators of patients' attitudes toward self-care in order to design population-adjusted approaches to influence human behavior.…”
Section: Health Care Models’ Performancementioning
confidence: 99%
“…Type 1 Diabetes (Dm1) is a chronic metabolic condition caused by an absolute insulin deficiency [ 1 ] brought about by the autoimmune destruction of pancreatic β-cells. Treatment includes behavioral and metabolic self-care measures [ 2 ] like proper nutrition, avoidance of toxic habits such as tobacco and alcohol consumption, and regular physical exercise [ 3 ]. It also includes insulin administration, self-monitoring of blood glucose, and the detection and treatment of hypoglycemia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%